Fermentation quality, bacterial community, and predicted functional profiles in silage prepared with alfalfa, perennial ryegrass and their mixture in the karst region - Fan, Xueying; Xie, Zhiming; Cheng, Qiming; Li, Maoya; Long, Jianhua; Lei, Yao; Jia, Yushan; Chen, Yulian; Chen, Chao; Wang, Zhijun (Frontiers in Microbiology, 2022)
There is little information regarding the dynamics of fermentation products and the bacterial community in silage prepared with alfalfa (MS), perennial ryegrass (LP), and their mixture in the karst region. In this study, we explored the effects of combining MS with LP in different ratios (100% MS, 70% MS+30% LP, 50% MS+50% LP, 30% MS+70% LP and 100% LP) (with fresh matter) on silage chemical compositions, fermentation quality and bacterial communities during the ensiling process. Each treatment was prepared in triplicate and stored at room temperature (22–25 °C) for 7, 15, and 45 days. The dry matter (DM) and water-soluble carbohydrate contents of silages increased as the LP proportion in the mixed silage increased; at 45 days, the 70% MS+30% LP, 50% MS+50% LP and 30% MS+70% LP silages contained higher (P < 0.05) CP content than the 100% MS and 100% LP silages. The 30% MS+70% LP and 100% LP silages exhibited lower (P < 0.05) pH and higher (P < 0.05) LA content than other silages; at 45 days, no silages contained PA or BA. As fermentation proceeded, the abundance of harmful (Enterobacteriaceae and Sphingomonas) and beneficial (Lentilactobacillus, Lactiplantibacillus, Secundilactobacillus and Levilactobacillus) microorganisms decreased and increased, respectfully, as the LP proportion in the mixed silage increased. Meaningfully, the 30%MS+70%LP and 100%LP silages had the stronger capacity of fermentation and weaker capacity of nitrate reduction than other silages. Thus, adding LP could improve the fermentation quality of MS silage by changing the microbial composition; furthermore, ensiling 30% alfalfa with 70% ryegrass can produce high-quality silage in the karst region.